Handbook of gender and women's studies - Davis, Kathy; Evans, Mary; Lorber, Judith (Sage, 2006)
Gender and women's studies is one of the most challenging fields within the social sciences - the dynamics of gender relations and the social and cultural implications of gender constructions offer a lively forum of debate. The Handbook of Gender and Women's Studies presents a comprehensive and engaging review of the most recent developments within the field, including the study of masculinity, the feminist implications of postmodernism, the 'cultural turn' and globalization. The authors review current research and offer critical analyses of women's and gender studies in work, the welfare state, family, education, religion, violence and war and feminist global politics. Edited by three leading academics from Europe and the United States, and with 25 chapters written by scholars based throughout the world, the Handbook situates the most important debates in the field within a uniquely international and interdisciplinary context. The Handbook is a useful introduction to gender theory and an exciting starting-point for fresh debates.